Rancang Bangun Mesin Pengupas Buah Pinang - Ade Hendra; Firman Ridwan (Department of Mechanical Engineering, Universitas Andalas, 2017)
In daily life, betel nut is widely used as ingredients of medicines, cosmetic materials and even clothing. Most of rural comunities conventionally process the Betel nut, hence the quality of betel nut has become less. To overcome this, a tool which has a high selling price and save production costs was made. This study aims to develop the skin peel machine. The result shown that the machine was capable to peel 1,066 second/piece using AC motor ¼ hp as an actuator.